Cost-effectiveness of uterine tamponade devices for the treatment of postpartum hemorrhage: A systematic review - Vogel, Joshua P. (2020)
Background: Uterine tamponade is widely promoted for treating refractory postpartum hemorrhage (PPH); however, its cost‐effectiveness may vary depending on unit costs and setting. Objective: To review available data on cost‐effectiveness of uterine tamponade devices when used for PPH treatment. Search strategy: PubMed and EMBASE were searched (1980 to January 2020), as well as the National Health Services Economic Evaluation database from inception (1995) to March 2015. Selection criteria: Eligible studies were any type of economic evaluation, or effective‐ ness studies that provided cost or economic data. Data collection and analysis: Two reviewers independently screened studies, extracted data, and assessed quality. Main results: Eleven studies using a range of devices (condom catheter, uterine suc‐ tion devices, Bakri, Inpress, Ellavi) were identified. Cost of condom catheter devices or kits ranged from US$0.64 to US$6, whereas purpose‐designed device costs were up to US$400. Two studies that took a health system perspective assessed the cost‐ effectiveness of using uterine balloon tamponade and suggested that it was highly cost‐ effective because of the low cost per disability‐adjusted life‐year averted, although both used effect estimates from case series. Conclusions: Evidence on the cost‐effectiveness of uterine tamponade devices was limited and not generalizable. Rigorous economic evaluations based on updated effect estimates are needed.